Additional Chromosomal Abnormalities in Chronic Myeloid Leukemia Patient Treated with First-Line Tyrosine Kinase Inhibitor Therapy: Good or Poor Prognosis? - Wulyo Rajabto; Noviana Joenputri (Interna Publishing, 2022)
A 33-year-old male came to Policlinic of Hematology-Medical Oncology Dr. Cipto Mangunkusumo General Hospital for routine control of chronic myeloid leukemia (CML) treatment. He was treated with Imatinib Mesylate (IM) for two years. At the beginning of therapy, he showed good treatment response. However, after two years of treatment, he lost complete hematological response (CHR) occured and major molecular response (MMR) was not achieved. This demonstrated drug resistance even with good compliance. Evaluation of therapy through cytogenetic karyotype testing showed complex additional chromosomal abnormalities (ACA) in addition to the Philadelphia chromosome (Ph). Tyrosine kinase inhibitor (TKI) therapy in this type of patients should be replaced with other alternative TKIs. A mutation profiling test is needed to determine alternative TKI. Monitoring in the treatment of CML patients is very important. The presence of ACA indicates disease progression and poor prognosis. Time to change therapy in CML patients must be done appropriately based on the results of hematological, molecular, and cytogenetic testing.